Reduced specificity of autobiographical memory: a mediator between rumination and ineffective social problem-solving in major depression? - Raes, F; Hermans, D; Williams, J; Demyttenaere, K; Sabbe, B; Pieters, G; Eelen, P (2005)
BACKGROUND: Depressed individuals display a deficit in effectively solving social problem situations (e.g., []). Recent research suggests that rumination may interfere with such effective problem-solving (e.g., []). However, little is known, as yet, about the mechanisms that are underlying this relation between rumination and poor problem-solving. The present study investigated the role of reduced specificity of autobiographical memories as a mediator of this relationship. METHODS: 24 depressed patients (15 women) completed the Autobiographical Memory Test (AMT), the Means-Ends Problem-Solving Task (MEPS), the Ruminative Response Scale (RRS) and the Rumination on Sadness Scale (RSS). RESULTS: Consistent with previous studies, rumination, ineffective problem-solving and reduced memory specificity were significantly associated. Regression analyses further extended these findings by showing that reduced memory specificity mediated the association between rumination and problem-solving effectiveness. LIMITATIONS: The correlational nature of this study limits to some extent the conclusions that can be drawn on the directionality of the observed relationships. CONCLUSIONS: Results offer support for the idea that lack of autobiographical memory specificity mediates the known relationship between rumination and poor problem-solving.